Katy Gardner and David Lewis. Anthropology and Development: Challenges for the Twenty-First Century. London: Pluto Press. 2015 (Second Edition). 240 page. Price £24.99 (The Pakistan Development Review, 2020)
The book entitled Anthropology and Development: Challenges for the TwentyFirst Century by Gardner and Lewis (2015) is the second edition of their previous book entitled Anthropology, Development and the Post-Modern Challenge, which was published in 1996. This second book incorporates recent issues that emerged since the first edition was released two decades ago. As the world keeps on changing, there are always new pressing issues that exert a significant influence upon development work to which an anthropological perspective has much to contribute.